2022
DOI: 10.1002/celc.202200237
|View full text |Cite
|
Sign up to set email alerts
|

A photoelectrochemical sensor combining CS−GSH−CuNCs and xanthine oxidase for the detection of xanthine

Abstract: A photoelectrochemical (PEC) sensor combining chitosan‐coated and glutathione‐protected copper nanocluster (CS−GSH−CuNCs) with peroxidase‐like activity and xanthine oxidase (XAO) was developed for rapid detection of xanthine. Firstly, CS−GSH−CuNCs was prepared by glutathione (GSH) reduction using chitosan (CS) as protective agent, and then was modified on titanium dioxide nanoparticles (TiO2 NPs)/ITO electrode which was prepared by sintering titanium dioxide (TiO2) on the ITO electrode surface by high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…The electrical impedance of the electrode increases to maximum. This is because AuNPs accumulate on the electrode surface, resulting in an increased e --h + recombination probability in CS-GSH-CuNCs and a reduced transfer of photogenerated electrons to the electrode [34]. However, when Met is present, AuNPs gathered on the electrode surface fall off and bind with Met because the interaction between Au and S is stronger than the interaction between Au and N [37,38,42], and the electrode conductivity is enhanced and the impedance is reduced (curve f).…”
Section: Eis Of Different Modified Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical impedance of the electrode increases to maximum. This is because AuNPs accumulate on the electrode surface, resulting in an increased e --h + recombination probability in CS-GSH-CuNCs and a reduced transfer of photogenerated electrons to the electrode [34]. However, when Met is present, AuNPs gathered on the electrode surface fall off and bind with Met because the interaction between Au and S is stronger than the interaction between Au and N [37,38,42], and the electrode conductivity is enhanced and the impedance is reduced (curve f).…”
Section: Eis Of Different Modified Electrodesmentioning
confidence: 99%
“…The detection performance of PEC sensors is closely related to the modified photosensitive materials. It is demonstrated that chitosan-coated and glutathione-protected copper nanocluster/titanium dioxide nanoparticles (CS-GSH-CuNCs/TiO 2 NPs) are a good photosensitive composite [34]. Photoexcitation at a wavelength of 365 nm causes the electrons in a copper nanocluster to move from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO) [35].…”
Section: Introductionmentioning
confidence: 99%